Estratégias ativistas no design - Batista, Marcelo Vianna (Universidade do Vale do Rio dos Sinos, 2023)
The proposal of the thesis is to understand activist strategies in design, recognizing "activism" and "strategies" as boundaries of knowledge in the field of design that we seek to promote advances in. To achieve this, the thesis is developed in three methodological movements. In the first movement, we conducted a literature review examining a) scientific productions on Activism; b) Activist Design, design in which activist characteristics are recognized; and c) strategies and Strategic Design, developing a provisional theoretical framework on activist strategies in design. In the second movement, we conducted observation, experimentation, and analysis of activist strategies in the empirical field in five experimental practices (Voices for Science, Afrodite Gorda, The Church of Entrepreneurship, Reddit vs. Stock Market, and the cases “Tudo bem por aí?” and “Tela... Sala de Espera”), in which qualitative methods were chosen to consider the particularity of each experimental practice, adopting reporting as a way of providing in-depth presentation of the activist situations presented. One by one, the practices are presented with a) pertinent contextualization; b) clarifications about the given contingencies; c) description of the observed event in this contingency; d) what the situation reveals about activist action; and, finally, e) the development of a proposal for activist strategies in design based on the analysis of what the practices revealed, which was positioned in the theoretical framework. The third movement adopts the seminar method, bringing the arguments developed in the first and second movements about activist strategies in design for debate and reflection with a) Brazilian authors with scientific production on Design and Activism, and b) Brazilian individuals who use the hashtag #designativista between November and December 2022. At the end, we present a general overview of the course of these four years of production, highlighting what is at stake when we talk about activism in design, and our final argument about activist strategies in design with an emphasis on diplomacy and humor: these strategies are more than just screaming for 'STOP' and assume a 'well, let's see' that slows down and promotes other views on the activist situation, and cause 'damage', but in a surreptitious way, on the margins of direct confrontation.
Keywords: Design; Ativismo; Estratégia; Design estratégico; Práticas experimentais; Diplomacia; Humor; Activism; Strategy; Strategic design; Experimental practices; Diplomacy; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial